The role of reinforcement orientation on the damage evolution of AlSi12CuMgNi + 15% Al2O3 under compression. (September 2016) - Cabeza, Sandra; Mishurova, Tatiana; Bruno, Giovanni; Garcés, Gerardo; Requena, Guillermo
Abstract: Internal damage of an AlSi12CuMgNi alloy reinforced with planar random short fibres has been investigated after compression. This damage strongly influences the load partition between matrix and reinforcement. For fibres perpendicular to the applied load, breakage and interconnected cracks appear in significantly higher volume fraction than with fibres parallel to load. Graphical abstract: